Термодинамическая эффективность каскадной утилизационной энергетической установки - Редько, А. А.; Компан, А. И.; Редько, А. Ф. (НТУ "ХПИ", 2013)
Наведені чисельні результати дослідження ефективності циклів утилізаційної каскадної енергетичної установки з різноманітними органічними робочими речовинами. Показана можливість їх застосування при температурі відхідних газів паливовикористовуючого агрегату до 350–400 °С.

In article numerical research results of efficiency utilization cascade power plant cycles with different organic working substances are considered. It is showed possibility of their use at a temperature of flue gases heat consuming unit up to 350–400 °С.
The thermodynamic efficiency of the cascade utilization of power plant
Keywords: топливно-энергетические ресурсы; отопительные котельные системы; топливоиспускающие агрегаты; промышленные печи; КПД; продукты сгорания